Effectiveness and Dose of Carvedilol Therapy In Children with Dilated Cardiomyopathy: A Prospective Randomized Double-Blinded Trial - Zeinab S. Seliem; Sonia A. El Saiedi; Reem I. Esmail; Rania M. H. El Kaffas; Mohamed Meabed; Baher M. Hanna (Cairo University, Faculty of Medicine, Department of Pediatrics, 2021)
Background: The efficacy and safety of the beta blocker carvedilol in pediatric patients with chronic heart failure (CHF) has not been fully established till now. Aim of the Work: To assess the role of carvedilol in the treatment of children with dilated cardiomyopathy, to demonstrate its efficacy, tolerability and determine the least effective dose. Patients and Methods: We conducted a double-blind, placebo-controlled study of 53 children with dilated cardiomyopathy (DCM). Patients were randomly assigned to receive either placebo (26 patients) or carvedilol (27 patients) added to the standard CHF therapy that consists of angiotensin-converting-enzyme inhibitor and diuretics. The carvedilol group was further subdivided into 2 groups according to the received dose of carvedilol. Subgroup I (11 cases) received carvedilol dose of 0.01-0.09 mg/kg/day and subgroup II (16 cases) received carvedilol with dose increments every 2 weeks from 0.01-0.2 mg/kg/day. All patients were followed up for four months after reaching the target dose. Results: The end results of the study showed that there was a significant improvement in Ross heart failure class, fractional shortening (FS), left ventricle end systolic dimension (LVESD) and left ventricle end diastolic dimension (LVEDD) in patients of the study group which was not achieved in the control group. On the other hand there was no statistically significant difference between sub groups I and II regarding the end point. Carvidolol was well tolerated, with no side effects or drug interaction reported. Conclusion: Addition of carvedilol to standard anti-failure therapy is of beneficial effect and is well tolerated in children with CHF on top of DCM. There may be no need for carvedilol dose up- titration at least for the first months of treatment.